Gender Identity in Soap Operas: The Social Representation of São-Borjan Transgender Individuals in "A Força do Querer" (Interdisciplinary Studies Journal, 2021)
The objective is to conduct a reception study inspired by the characters "Ivana" and "Nonato" in the soap opera "A Força do Querer." We also aim to understand whether the transgender individuals in the city of São Borja feel represented by the characters created by playwright Glória Perez. The theoretical framework is based on the multiple mediations of Orozco Gómez (1997), soap operas, identity, gender, and reception. We highlight that the discourse of the telenovela diverges in some aspects from the daily life of transgender individuals in São Borja, partially showcasing the representativity of these subjects.
Keywords: Soap Opera; Identity; Communication; Culture